The development of cisplatin resistance in neuroblastoma is accompanied by epithelial to mesenchymal transition in vitro. Issue 2 (10th August 2015) - Piskareva, Olga; Harvey, Harry; Nolan, John; Conlon, Ross; Alcock, Leah; Buckley, Patrick; Dowling, Paul; Henry, Michael; O'Sullivan, Finbarr; Bray, Isabella; Stallings, Raymond L.
Highlights: Cisplatin induced cross resistance to temozolomide, etoposide and irinotecan. Proteomic profiling of three cisplatin resistant neuroblastoma cell sublines. Altered proteins had cellular growth and proliferation, cell death and survival classifications. Increased migration of SK-N-ASCis24 correlates with elevated levels of MYH9 and ACTN4. EMT and increased cell migration are associated with drug resistance in SK-N-ASCis24. Abstract: Neuroblastoma is a challenging childhood malignancy, with a very high percentage of patients relapsing following acquisition of drug resistance, thereby necessitating the identification of mechanisms of drug resistance as well as new biological targets contributing to the aggressive pathogenicity of the disease. In order to investigate the molecular pathways that are involved with drug resistance in neuroblastoma, we have developed and characterised cisplatin resistant sublines SK-N-ASCis24, KellyCis83 and CHP-212Cis100, integrating data of cell behaviour, cytotoxicity, genomic alterations and modulation of protein expression. All three cisplatin resistant cell lines demonstrated cross resistance to temozolomide, etoposide and irinotecan, all of which are drugs in re-initiation therapy. Array CGH analysis indicated that resistant lines have acquired additional genomic imbalances. Differentially expressed proteins were identified by mass spectrometry and classified by bioinformatics tools according to their molecular and cellular functions and their involvement into biological pathways. Significant changes in the expression of proteins involved with pathways such as actin cytoskeletal signalling (p = 9.28E−10), integrin linked kinase (ILK) signalling (p = 4.01E−8), epithelial adherens junctions signalling (p = 5.49E−8) and remodelling of epithelial adherens junctions (p = 5.87E−8) pointed towards a mesenchymal phenotype developed by cisplatin resistant SK-N-ASCis24. Western blotting and confocal microscopy of MYH9, ACTN4 and ROCK1 coupled with invasion assays provide evidence that elevated levels of MYH9 and ACTN4 and reduced levels of ROCK1 contribute to the increased ROCK1-independent migratory potential of SK-N-ASCis24. Therefore, our results suggest that epithelial-to-mesenchymal transition is a feature during the development of drug resistance in neuroblastoma.